Characterization of human skin equivalents developed at body's core and surface temperatures. (21st May 2019) - Mieremet, Arnout; van Dijk, Rianne; Boiten, Walter; Gooris, Gert; Bouwstra, Joke A.; El Ghalbzouri, Abdoelwaheb
Abstract: Human skin equivalents (HSEs) are in vitro developed three‐dimensional models resembling native human skin (NHS) to a high extent. However, the epidermal lipid biosynthesis, barrier lipid composition, and organization are altered, leading to an elevated diffusion rate of therapeutic molecules. The altered lipid barrier formation in HSEs may be induced by standardized culture conditions, including a culture temperature of 37°C, which is dissimilar to skin surface temperature. Therefore, we aim to determine the influence of culture temperature during the generation of full thickness models (FTMs) on epidermal morphogenesis and lipid barrier formation. For this purpose, FTMs were developed at conventional core temperature (37°C) or lower temperatures (35°C and 33°C) and evaluated over a time period of 4 weeks. The stratum corneum (SC) lipid composition was analysed using advanced liquid chromatography coupled to mass spectrometry analysis. Our results show that SC layers accumulated at a similar rate irrespective of culture temperature. At reduced culture temperature, an increased epidermal thickness, a disorganization of the lower epidermal cell layers, a delayed early differentiation, and an enlargement of granular cells were detected. Interestingly, melanogenesis was reduced at lower temperature. The ceramide subclass profile, chain length distribution, and level of unsaturated ceramides were similar in FTMs generated at 37°C and 35°C but changed when generated at 33°C, reducing the resemblance to NHS. Herein, we report that culture temperature affects epidermal morphogenesis substantially and to a lesser extent the lipid barrier formation, highlighting the importance of optimized external parameters during reconstruction of skin.